PENILAIAN OTENTIK: : TEKNIK DAN INSTRUMEN DALAM KURIKULUM 2013 - Reresi, Marsianus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2015)
In this article concrete answers are provided to attain a genuine estimation. The article is focused on this question: “What is a genuine estimation?” Teachers will be able to carry out a genuine estimation when they thoroughly understand what is meant by genuine estimation. Genuine estimation stresses the estimation of the process. Thus the genuine estimation becomes the complete focus in matters of formal education.